PHYSIOLOGICAL MECHANISMS AND FACTORS AFFECTING FEMALE FERTILITY RESTORATION FOLLOWING FIRST CHILDBIRTH - Ismailova Shoira Tolkunovna; Tuhtasinova Zulkhumor Ahmadjon kizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Restoration of female fertility following first childbirth is a complex physiological process influenced by hormonal, anatomical, and environmental factors. The postpartum period involves dynamic changes in the hypothalamic-pituitary-ovarian (HPO) axis, lactational regulation, uterine involution, and maternal health status, all of which affect ovulation, menstruation, and overall reproductive potential. This study investigates the physiological mechanisms and key factors influencing fertility restoration after first childbirth. A cohort of 210 women aged 20–35 years was followed over the first 12 months postpartum. Hormonal assays (prolactin, FSH, LH, estradiol, and progesterone), menstrual cycle tracking, ovulation monitoring, and clinical assessments were performed to evaluate recovery patterns. Results indicate that lactation, maternal age, and baseline gynecological health are the most significant determinants of fertility restoration. Exclusive breastfeeding prolongs postpartum amenorrhea and delays ovulation, while maternal age and pre-existing gynecological conditions modulate the speed and regularity of reproductive recovery. These findings provide critical insights into postpartum fertility regulation and have important implications for clinical practice, including fertility counseling, family planning, and individualized postpartum care.